Hoyle's Games improved [...] with The established |Rules of Game. By [...] (Rice James a. Comp., 1796)
Schach S. 166-175
A short treatise on the Game of Chess. Das erste in America gedruckte Buch, in dem etwas über Schach enthalten ist
Keywords: tenis; szachy